Analysis of production and investment efficiency in the Mexican food industry: Application of two-stage DEA - Flegl, Martin; Sanchez Juarez, Isaac Leobardo; Jiménez, Carlos; Matus, Edgar (2022)
The food industry in Mexico is a precarious sector and lags behind other manufacturing industries, it is made up mainly of small and medium-sized enterprises. Its importance in the food assurance of the country requires strategic monitoring of the yield and efficiency variables that allow successful interventions to improve results. Commonly, the efficiency in the agriculture sector is evaluated as a one-stage data envelopment analysis (DEA) process using a specific set of variables. In this article, we applied a two-stage process to evaluate the efficiency in the Mexican food industry. The first stage evaluates the efficiency of the production, whereas the second stage evaluates the efficiency of investments in the sector. The process is demonstrated on a sample of 1 672 Mexican municipalities using data from 2014 and 2019 Census. The results indicate a growth in production efficiency with significant differences between regions. Moreover, the results also revealed very low investment efficiency in the whole food sector with a negative tendency.